MANAJEMEN RISIKO PADA PELAKSANAAN PROYEK KONSTRUKSI GEDUNG PEMERINTAH DI KOTA DILI – TIMOR LESTE - P.M Marques, Octavio; Alit K. Salain, I M.; Yansen, I W. (JURNAL SPEKTRAN, 2014)
Building project as one of the construction services are filled with varying risks during the construction phase of the project implementation. At the stage of the project implementation, risks may arise either the risk of time, cost and those which affect the quality of the project. Therefore, we need to understand the risks at the construction phase and mitigation to the risks to meet in execution of project based on initial planning. The study was conducted to identify the risks in the implementation of construction projects of government buildings by using survey methods that aim to get the opinion of the respondents regarding the risks at implementation of the government building construction projects in the city of Dili - Timor Leste. Further, it was done a risk assessment to determine the major or main risks. Major risk is controlled through mitigation measures and allocation of risks to the parties directly involved in construction projects such as Project Owner, Technical Supervisor, Consultant Design, Consultant Supervision and Contractor. The analysis used in this study is a qualitative analysis. The results showed 64 risks identified in the implementation of construction projects there are 10 government buildings risks (16%) with an unacceptable category, 18 risks (28%) with the undesirable category, 28 risks (44%) with acceptable category and 8 risks (12%) with negligible category. Ownership of major / main risk to the parties directly involved in the implementation of construction projects such as the project owner, technical supervisor, consultant design, consultant supervision and contractors. The project Owner and Technical Supervision (Department of Public Works) is expected to further enhance the ability to manage projects so not throwing responsibility in managing government projects. consultant design and sonsultant supervision to be more careful in design till supervision during the implementation period so as to meet the cost, quality and time planned. Contractors are expected to further improve the performance of the building construction project.
Keywords: implementation risks, construction projects, government buildings